The Socratic Method in a Foreign Language Classroom - Darginavičienė, Irena (Acta Paedagogica Vilnensia, 2007)
The article considers the use of Socratic Dialogue when it is applied in teaching English for specific purposes. It looks into the functioning of Socratic Method in the English language classroom for Law and Public Administration students. The investigation employs a two-fold techniques. On the one hand, the emphasis is laid on the self-confidence in one's own thinking. Therefore, in the form of the Socratic Dialogue this method encourages students to reason and think independently and critically. On the other hand, the development of the thinking process calls for the use of a very specific vocabulary which fosters students to develop foreign language skills. Students have to master English for Law and English for Public Administration vocabulary as well as complicated syntactical and grammatical structures. The article also gives an account of a classroom discussion on a topic "What is autonomy?". Students assume that autonomy is a matter of internal personal experience rather than phenomenon which is perceived objectively in the world.
Keywords: Socratic Method; Socratic Dialogue; critical thinking; questioning techniques; universal intellectual standards; consensus; dissensus